De-escalation treatment of human papillomavirus-positive oropharyngeal squamous cell carcinoma: an evidence-based review for the locally advanced disease. Issue 3 (May 2018) - Stock, Gustavo T.; Bonadio, Renata R.C. Colombo; de Castro, Gilberto
Abstract : Purpose of review: Oropharyngeal cancer (OPC) incidence is increasing worldwide, especially in developed countries where it seems to be etiologically related to the elevating rates of high-risk human papillomavirus (HPV) infection. Considered a distinct disease because of its weak correlation with the traditional risk factors (tobacco use and alcohol), it has different patterns of survival outcomes, locoregional and distant failure, generally with better prognosis independently of the treatment. The standard therapeutic approach for locally advanced (LA) OPCs includes radiation therapy with concurrent chemotherapy, resulting in severe toxicities with negative impacts in quality of life (QoL). Considering this, efforts emerged to de-intensify treatment modalities in selected patients and achieve less morbidity while maintaining the favorable outcome. Recent findings: Several de-escalated treatment strategies for HPV-related OPCs have been proposed to date with some of them being assessed in ongoing clinical trials. The main approaches encompass: minimally invasive surgery and reduced adjuvant treatment; antiepidermal growth factor receptor (EGFR) monoclonal antibodies (mAbs) as alternative to chemotherapy concurrent with radiation therapy; adjusted radiation therapy dose intensity in responders to induction chemotherapy; reduced-dose radiation therapy. Summary: There is still a lack of evidence to support de-intensification treatment for HPV-positive LA-OPC in clinical practice, and it remains investigational. Ongoing trials based on risk stratification might identify subgroups with greatest benefits of de-escalation strategies, reducing treatment morbidity without constituting the favorable prognosis.